2022
DOI: 10.3390/jcm11247342
|View full text |Cite
|
Sign up to set email alerts
|

The Course of COVID-19 in Patients with Systemic Autoimmune Rheumatic Diseases

Abstract: Patients with systemic autoimmune rheumatic disease (SARD) have increased susceptibility to viral infections, including SARS-CoV-2. The aim of this study was to analyse the SARD patient population with COVID-19 (coronavirus disease 2019) in terms of baseline characteristics, severity, course and outcomes of the disease compared with the non-SARD group, and to identify factors associated with prognosis, including remdesivir therapy efficacy. Retrospective study comprised 8220 COVID-19 cases from the SARSTer dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
0
6
0
2
Order By: Relevance
“…99 unique studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , ...…”
Section: Resultsunclassified
“…99 unique studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , ...…”
Section: Resultsunclassified
“…Several studies have challenged the idea that the presence of ARDs does not impact COVID‐19‐related inpatient outcomes. For instance, a national database analysis conducted in 30 Polish centers by Rorat et al found that patients with ARDs hospitalized with COVID‐19 had longer LOS and higher mortality rates compared with patients without ARDs ( 11 ). Supporting these results, a multicenter study carried out in Oman by Al‐Adhoubi et al also found increased mortality in COVID‐19 hospitalizations among those with ARDs ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these plausible mechanisms for more severe disease presentation and the noted increases in incidence and hospitalization, the impact of ARD presence on inpatient outcomes in those with COVID‐19 is still debated. Some studies have shown ARDs to have no significant impact on inpatient COVID‐19 outcomes ( 5 , 6 , 7 , 8 , 9 ), whereas others have shown significant increases in many clinical factors, including mortality and rates of mechanical ventilation ( 10 , 11 , 12 , 13 , 14 ). To address this important clinical question, we conducted a retrospective cohort study to evaluate outcomes in individuals with ARDs hospitalized with COVID‐19 in 2020 using the largest national inpatient database in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…In the Global Rheumatology Alliance Physician Reported Registry, Strangfeld et al 4 showed that COVID‐19‐related mortality was associated with rheumatic disease‐specific factors such as moderate‐high disease activity and specific drugs such as sulfasalazine and rituximab, along with known risk factors (male gender, older age, classical comorbidities). Rorat et al 15 have recently compared the COVID‐19 disease course between 185 patients with AIRDs and 8035 patients without AIRDs. The disease course was more severe in AIRD patients.…”
Section: The Factors Possible Effects On Covid‐19 Outcomementioning
confidence: 99%